2020
DOI: 10.1021/acs.macromol.0c00134
|View full text |Cite
|
Sign up to set email alerts
|

Mesolytic Versus Homolytic Cleavage in Photochemical Nitroxide-Mediated Polymerization

Abstract: Time-dependent density functional theory calculations have been performed to study the photocleavage reactions of chromophore-functionalized alkoxyamines in nitroxide-mediated photopolymerization. Two case studies were considered: azaphenalene derivatives and benzophenone-based alkoxyamines. For the azaphenalenes, we show that the expected homolysis pathway is actually inaccessible. Instead, these alkoxyamines exhibit low-lying excited states that exhibit an electronic structure about the nitroxide moiety simi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…26 All open-and closedshell SCF calculations were performed with density functional theory (DFT), and excited state energies and electrostatic surfaces were obtained with TD-DFT. As in our previous study, 21 the meta-GGA, M06-2X density functional 27 was employed alongside the 6-31+G(d,p) basis set for all types of calculation, as this combination of functional and basis set has been shown to produce ground and excited state energies with qualitative accuracy. 28 Solvent effects were obtained with the SMD universal solvent model, 29 using ethyl ethanoate as the solvation environment so as to mimic a bulk acrylic monomer-like solvent.…”
Section: Computational Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…26 All open-and closedshell SCF calculations were performed with density functional theory (DFT), and excited state energies and electrostatic surfaces were obtained with TD-DFT. As in our previous study, 21 the meta-GGA, M06-2X density functional 27 was employed alongside the 6-31+G(d,p) basis set for all types of calculation, as this combination of functional and basis set has been shown to produce ground and excited state energies with qualitative accuracy. 28 Solvent effects were obtained with the SMD universal solvent model, 29 using ethyl ethanoate as the solvation environment so as to mimic a bulk acrylic monomer-like solvent.…”
Section: Computational Methodologymentioning
confidence: 99%
“…[14][15][16][17][18][19][20] Recently we studied two systems that are able to control some but not all classes of monomer tested, 15,17 and have shown that this variable behaviour may be in part due to a preference for mesolytic rather than homolytic dissociation (Scheme 2). 21 Mesolytic cleavage, which occurs from the 𝑛 ! 𝜋 * rather than 𝜋𝜋 * or 𝑛 # 𝜋 * excited states, results in the formation of a radical and a cation.…”
Section: Scheme 1 Nitroxide Mediated Polymerizationmentioning
confidence: 99%
“…This said, the inherent tunability of Blatter radicals may well come as an advantage in more bespoke photo-and electro-induced polymerizations, both of which have curried great interest in recent literature. [179][180][181][182][183] Figure 34. Control equilibrium in Blatter-mediated radical polymerization, illustrated using Blatter's radical as the control agent for a generic polymer PN.…”
Section: Synthetic Applicationsmentioning
confidence: 99%
“…It is well-known that different substitutions (primary, second vs tertiary carbon) of R groups in NMP and ATRP initiators have significant effects on the activation rate coefficients. A penultimate unit effect in NMP and ATRP initiators (the initiators have identical terminal units but different penultimate units) has been comprehensively investigated on their activation rates by using experimental analysis and simulation modeling. Meanwhile, the effects of stereochemical structures on the activation kinetics in NMP and ATRP have also been studied with considerable efforts. Matyjaszewski and co-workers synthesized a series of model dimeric alkyl bromide initiators with diverse combinations of methyl acrylate (MA), methyl methacrylate (MMA), and tert -butyl acrylate ( t BA), which have two diastereomers in most cases.…”
Section: Introductionmentioning
confidence: 99%